(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Every business has changed its strategy in the era of technology and stiff competition. To have a competitive edge, it has become substantial for businesses to adopt digitalization as it saves time and creates new opportunities. However, this disruption does not occur at the organizational level; it has societal and environmental implications. At the business or organizational level, it has fundamentally transformed every functionality, and the HR function is one of them. It offers new tools and work methodologies to enhance employee efficiency, engagement, and decision-making. Digital technology has streamlined various HR processes such as recruitment, selection, training and development, performance management, etc. Tools like artificial intelligence and HR analytics have revolutionized workforce planning and management, offering real-time feedback and increasing efficiency. It has enabled HR professionals to make informed decisions based on extensive data insights. Besides offering benefits, digitalization also presents challenges that need to be considered. The firms must adopt digital tools and tactics to improve their HR operations and stay competitive. The present study explores the impact of digitalization on HR practices and offers insights into the challenges and opportunities it presents. This article attempts to determine how digitalization impacts HR practices and its significant challenges. This theoretical discussion gives a brief review of the impact and challenges of HR digitalization in the current scenario. For this study, the researcher reviewed the most recent research findings from the scientific literature and business practice and used an integrative research method. This research article is becoming an essential voice in HR digitalization and its impact on HR practice. It will allow HR professionals and academia to develop more insights into reaping the benefits of digitalization and concentrating on how it can be strategically advantageous for business organizations in this technological era.